The health behaviors differences among male and female school-age adolescents in the Middle East and North Africa region countries: a meta-analysis of the Global School-based Student Health Survey data - Achak, Doha; Azizi, Asmaa; El-Ammari, Abdelghaffar; Marfak, Ibtissam Youlyouz; Saad, Elmadani; Nejjari, Chakib; Hilali, Abderraouf; Peltzer, Karl; Marfak, Abdelghafour (Frontiers in Public Health, 2024)
Background Understanding gender disparities in adolescent health behaviors is crucial for developing targeted health promotion strategies. This study uses data from the Global School-based Student Health Survey (GSHS) across 17 MENA countries to analyze gender differences in adolescent health behaviors, aiming to provide a comprehensive overview for both boys and girls. Methods This meta-analysis incorporates data from recent years of the GSHS, covering 17 MENA countries. The objective was to assess and compare health behaviors between adolescent girls and boys. A random-effects model was employed to calculate odds ratios for gender comparisons in these behaviors. Statistical analyses and modeling were performed using JAMOVI software. Results In most MENA countries, boys consumed more vegetables compared to girls. Girls were less likely to frequent fast food establishments (OR=0.82, 95% CI: 0.69-0.98) and generally exhibited better self-care behaviors. Boys reported a higher prevalence of physical altercations (OR=2.18, 95% CI: 1.88-2.51) and were more involved in fights (OR=3.00, 95% CI: 2.46-3.67). Girls were more likely to miss school without permission and were consistently described as kinder and more helpful across various income levels. However, in some countries such as Oman and Tunisia, boys missed school more frequently. There were no significant gender differences in parental oversight of homework or knowledge of students' activities, but girls were reported to have stronger parental relationships and better parental understanding of their problems and free time, with exceptions in Morocco and the Palestinian Territory-Gaza. Boys were more likely to engage in smoking (OR=3.57, 95% CI: 2.69-4.76) and other substance use. Conversely, girls reported higher levels of physical inactivity and loneliness, but also demonstrated greater kindness and helpfulness in school settings and stronger parental relationships. Conclusion Policymakers in the MENA region should develop and implement gender-specific interventions targeting key areas such as hygiene practices, physical activity, and substance use. By focusing on these targeted strategies, they can address the distinct health behaviors and needs of both boys and girls. Effective interventions in these areas are crucial for improving overall health outcomes and promoting healthier lifestyles, thereby enhancing adolescent health and well-being across the region.